STRATEGIES FOR TEACHING LISTENING TO YOUNG CHILDREN - Davronova , Umida Otabek qizi (Educational Research in Universal Sciences, 2023)
Teaching listening skills to young children is crucial for their language development and overall academic success. This paper explores effective strategies for teaching listening to young children, including the use of songs, stories, and games. The importance of creating a supportive and engaging learning environment is also discussed. Additionally, the paper highlights the role of technology in teaching listening skills, such as using audio recordings and interactive apps. Practical examples and activities are provided to illustrate the strategies discussed. Overall, this paper aims to provide educators with practical and effective techniques for teaching listening skills to young children.